2016
DOI: 10.1007/s00122-016-2728-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea

Abstract: A novel allele-specific Rfo marker was developed and proved to be effective for MAS of Rfo gene in B. oleracea background and six Ogu-CMS fertility-restored interspecific hybrids were created for the first time. Ogura cytoplasmic male sterility (Ogu-CMS) has been extensively used for Brassica oleracea hybrid production. However, because of maternal inheritance, all the hybrids produced by CMS lines are male sterile and cannot be self-pollinated, which prohibits germplasm maintenance and innovation. This proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
1
19
1
1
Order By: Relevance
“…Restorer gene was detected by FISH using C genome and BAC as fish probe while A genome of B. napus was as block (Fig 2c). Green signals were detected consistently in A genome not C genome of B. napus, which is different from previous restorer lines (7,21,23).…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…Restorer gene was detected by FISH using C genome and BAC as fish probe while A genome of B. napus was as block (Fig 2c). Green signals were detected consistently in A genome not C genome of B. napus, which is different from previous restorer lines (7,21,23).…”
Section: Plos Onecontrasting
confidence: 99%
“…However, not many studies linked this aspect to the radish-derived Ogu CMS in B. napus, the genetic behaviors of Ogu CMS restorer line as pollen donor or accepter remains unclear and is worthy of investigation. Moreover, molecular marker assisted breeding has been applied throughout the breeding history of Ogu-CMS restorer line in Brassica family [11,[21][22][23]. Rfo specific markers in canola were developed by Hu et al [21], while Tian et al [22] and Yu et al [23] applied to B. juncea and B. oleracea respectively, enabling previse selection for low glucosinolate within larger population.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on Ogura cytoplasm has revealed the molecular basis of male sterility and fertility restoration (Bonhomme et al 1992, Tanaka et al 2012, Brown et al 2003, Desloire et al 2003, Koizuka et al 2003, Uyttewaal et al 2008. As a result, genomic data are available for development of molecular markers to assist the selection of CMS and restorer lines (Kim et al 2007, Yu et al 2016.…”
Section: Pollination Control Methods In Different Vegetable Crops Bramentioning
confidence: 99%
“…The original source of inbred line T54S was derived from the Sakata commercial cultivar (Japan). The broccoli line T54C is derived from the popular Ogura-CMS line (Sakata, Japan) [54,55], and T54M was initially derived from the cabbage line 79-399-3 (our lab) [56,57]. All the plant materials were cultivated and improved by our lab (IVF-CAAS).…”
Section: Plant Materials and Agronomic Trait Investigationmentioning
confidence: 99%